Le'via Company / Nazrul bin Jimmy... [et al.] - Sabin, Mohd Al Hairrin; Linus, Hamizan; Osman, Hafizul; Fabian, Flora; Juanis, Mohd Rosman; Jimmy, Nazrul (2015)
Le'Via is a product to replace sugar and lemonade flavor added. This product suitable for all ages and it is good for our health. Our product is a new innovation and still does not have in market. Although our product still new in the market, it can promises better opportunities for us to invest because the concept of our product is different than other competitors. Our products can fulfill satisfaction of our future customer. The name of our products Le'Via is simple and direct to point which is stevia combination with lemonade. It is easy to understand and easily remembered because the term we use to define our product. It is also common and will not welcome confusion people thought when interpreting. We dare to take a risk because we believe that every opportunities lies in what we cannot see right now but can see in the future. One of the most important aspects that drive us to select this kind of business is because we realize the demand of the customer that need something new and will attract customers. Lastly, our business will be located at Center Point (Ground Floor) in Kota Kinabalu due to development of economic in that particular area that can attract local customer and tourists. We will find the best and profitable area to set our business. We believe that through effort and each partner contribution can achieve our stated objectives, vision and mission.